(untitled) (Journal of Enam Medical College, 2022)
Background: Granulomatous mastitis can be divided into idiopathic granulomatous mastitis and granulomatous mastitis occurring as a rare secondary complication of a great variety of other conditions such as tuberculosis and other infections, sarcoidosis and granulomatosis with polyangitis. Idiopathic granulomatous mastitis (IGM) is an uncommon benign chronic inflammatory disease which can clinically and radiographically mimic abscess or breast cancer. Definitive diagnosis was made by histopathology and exclusion of an identifying etiology. Optimal treatment has not been yet established. Objectives: The aim of this study was to report and describe the clinical signs, radiological findings, managements, clinical course, and clinical outcomes after treatment of IGM. Materials and Methods: We conducted a descriptive cross-sectional study on 28 patients with chronic GM in Enam Medical College & Hospital collected in 1 year. The patient characteristics, clinical presentations, radiological findings, microbiological workups, tissue pathology, treatment modalities, outcomes were analyzed. We evaluated only the response of wide local excision and assess the recurrence up to 2 years after surgery on the treatment modalities to find out the proper treatments for chronic GM patient. Results: Twenty eight patients were diagnosed as chronic granulomatous mastitis. FNAC was conducted before excision. Twenty seven patients had chronic granulomatous mastitis and one patient had tuberculosis on histopathology. In the first setting, 28 patients were treated by surgery. Thirteen patients out of 28 had open wound after performing an excision in which healing by secondary intention was done. Ten patients had undergone primary closure and no complications. Conclusion: Chronic GM is an uncommon benign disease which is hardly distinguished from malignancy. There is not a significant difference among treatment modalities in term of time-to-healing and recurrence of disease. The result shows that surgery is outperformed by the shortest healing time. However, the surgical treatment must be chosen with careful due to high rate of wound complications. Multimodality treatment is recommended as the proper treatments for chronic GM patient. J Enam Med Col 2020; 10(3): 174-178